KREATIVITAS UDJO NGALAGENA : STUDI KEBERHASILAN PENGEMBANGAN KREATIVITAS DI SAUNG ANGKLUNG UDJO (SAU) - Budiman Mahmud (Jurnal Vokasi Indonesia, 2015)
AbstractThis article is the result of qualitative research which focused on creativity, especiallycreativity Udjo Ngalagena in terms of personal, press, processes and products. The results showedthat the various potentials and support from the family, community and school (education) makesUdjo being personally creative. Personal creative and press factor gives strength to Udjo Ngalagenato continue and develop their creativity amid the challenges and conditions of the times. UdjoNgalagena succeeded in making angklung tradition into creative products in educational activities,production and performances regularly and formally at Saung Angklung Udjo (SAU) with referenceto the traditional values of Sunda. The existence and development of the SAU in Bandung, WestJava for almost a 50 years proves that Udjo Ngalagena succeeded in creating generations of creativeand successfully strengthen the local cultural existence.Keywords:. Creativity, Udjo Ngalagena, Saung Angklung Udjo